The Effect of Economic Literacy, and Financial Literacy on Financial Intelligence Students of Entrepreneur Campus Memorizing Al-Qur'an (KEPQ) - Priyo Utomo; syamsul Arifin (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: The purpose of this study was to determine the effect of Economic Literacy, Financial Literacy, on Financial Intelligence of Students in Entrepreneurship Campus Memorizing the Qur'an (KEPQ). Design/methodology/approach: The method in this research uses a quantitative approach with types the research used was ex post facto. Findings: The research was carried out in campus Entrepreneur Memor Al-Qur'an (KEPQ) Surabaya. Research limitations/implications: The limitation in the study uses two independent variables and one variable related to the Economic Literacy variable, the Financial Literacy variable, and the Student Financial Intelligence variable. Practical implications: The population numbered 120 people and the study sample was 93 people who were determined by the proportional random sampling technique. Originality/value: This research conducted in Entrepreneurship Campus Memorizing the Qur'an (KEPQ) Paper type: Research paper